A Great and Growing Rift. Issue 4 (3rd July 2020) - Gans, John A.
Abstract : As James Mann makes clear in his engaging dual biography, the world views and weaknesses of Colin Powell and Dick Cheney eventually undermined not just their relationship, but also American foreign relations.